CONTENT OF SOME ANTIOXIDANTS IN INTERCROPPED MAIZE AND SOY GRAIN - Dragičević, Vesna D.; Oljača, Snežana; Simić, Milena; Dolijanović, Željko; Kresović, Branka; Brankov, Milan (Journal of Agricultural Sciences (Belgrade), 2017)
Intercropping, as a combination of different crops at the same time and the same field enables interaction of their roots, improving plant growth and stress tolerance, thus improving nutritional quality of produced grains. The investigation was aimed to examine different cropping systems: intercropping with combination of alternating rows and alternating strips of maize and soybean, as well as single cropping, combined with different fertilization regimes (conventional, application of organic fertilizer, bio-fertilizer and control) on antioxidants content (glutathione (GSH), phenolics and yellow pigment (YP)) in red maize and black soy grain. Black soybean is richer in antioxidants than red maize. Season expressed the highest influence on the level of GSH, phenolics and YP in maize and soybean, while cropping system and fertilization regime influenced GSH and phenolics. Antioxidants level in grains with greater weight corresponded with increased GSH level for maize, as well as increased GSH and phenolics level for soybean, while smaller grains were characterised with the increased YP content. Generally, antioxidants content was increased mainly by alternating strips in maize grain and by alternating rows in soy grain. Bio-fertilizer expressed the highest impact on increase in GSH in maize grain and YP in soy grain, while organic fertilizer was important for acquiring of GSH and phenolics in soy grain.